1996
DOI: 10.1074/jbc.271.44.27770
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific, Calcium-regulated Interaction of the Synaptic Vesicle Proteins SV2 and Synaptotagmin

Abstract: The identification and functional characterization of proteins localized to synaptic vesicles has contributed significantly to our understanding of neurotransmission. Studies of synaptic vesicle protein interactions have both led to the identification of novel synaptic proteins and suggested hypotheses of protein function. Synaptic vesicle protein 2 (SV2), is an integral membrane glycoprotein present in all synaptic vesicles. There are two characterized isoforms, SV2A and SV2B. Despite their homology to transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
3
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 41 publications
7
129
3
1
Order By: Relevance
“…Biochemical studies have revealed many protein-protein interactions between different SV proteins (Bennett et al, 1992;Calakos and Scheller, 1994;Galli et al, 1996;Schivell et al, 1996). To assess whether localization of SNG-1 is mediated by protein-protein interactions with other SV protein(s), we examined SNG-1::GFP or native SNG-1 localization in mutants lacking distinct SV-associated proteins, including RAB-3 and RBF-1 (rabphilin), SNB-1, and SNT-1 (Table 1; Nonet et al, 1993Nonet et al, , 1997Nonet et al, , 1998; Staunton, Ganetzky, and Nonet, unpublished observations).…”
Section: Sng-1::gfp Localization Does Not Require Several Synaptic Prmentioning
confidence: 99%
“…Biochemical studies have revealed many protein-protein interactions between different SV proteins (Bennett et al, 1992;Calakos and Scheller, 1994;Galli et al, 1996;Schivell et al, 1996). To assess whether localization of SNG-1 is mediated by protein-protein interactions with other SV protein(s), we examined SNG-1::GFP or native SNG-1 localization in mutants lacking distinct SV-associated proteins, including RAB-3 and RBF-1 (rabphilin), SNB-1, and SNT-1 (Table 1; Nonet et al, 1993Nonet et al, , 1997Nonet et al, , 1998; Staunton, Ganetzky, and Nonet, unpublished observations).…”
Section: Sng-1::gfp Localization Does Not Require Several Synaptic Prmentioning
confidence: 99%
“…This question was prompted by the finding that mutations within the C2B domain of Drosophila synaptotagmin impair excitation-secretion coupling (DiAntonio and Schwarz 1994; Littleton et al 1993, Littleton et al 1994). A number of C2B–effector interactions have been identified including the following: AP-2 (Zhang et al 1994; Jorgensen et al 1995), SV2 (Schivell et al 1996), β-SNAP (Schiavo et al 1995), Ca 2+ channels (Kim and Catterall 1997; Sheng et al 1997), inositol polyphosphates (Fukuda et al 1995) and, finally, homo-oligomerization (Chapman et al 1996; Sugita et al 1996). Of these interactions, only oligomerization was promoted by Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…This use of Ponceau-S has been described previously (Klein et al, 1995;Moore and Viselli, 2000) and actual examples occur throughout the published literature (Schivell et al, 1996;Bakiri et al, 2000). Western blotting was performed under standard conditions using 5% milk in PBS with 0.3% Tween 20 as a blocking agent.…”
Section: Cell Fractionation and Western Blot Analysismentioning
confidence: 99%